Ultrabornological structures - V. Murali (International Journal of Mathematics and Mathematical Sciences)
The purpose of this note is to extend Warner's idea of bornological structures to cover non-locally convex situations and to develop a framework unifying several variations on an ultrabornological theme (for example, ultrabornological spaces, o-ultrabornological spaces, i-ultrabornological algebras). We do this by first generalising the concept of a structure on a vector space as defined by Warner.